Pengaruh Pengawasan Camat Terhadap Disiplin Kerja Pegawai Negeri Sipil Dikantor Kecamatan Langowan Selatan Kabupaten Minahasa - Manoppo, Fari; Posumah, Jhonny Hanny; Rares, Joyce Jacinta (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : Leaders must perform a management step that organizational goals can be achieved. One suchstep is to supervise the work discipline committed by people who are involved in an organization. thepurpose of this study was to determine whether there is influence camat supervision of the work disciplineat the office of the Civil Service South Minahasa District Langowan.This study is an explorative survey, with a quantitative approach. The population at the office of SouthMinahasa District Langowan.Results of simple correlation analysis shows that scrutiny Head positively correlated and real orsignificant to the discipline of civil servants working at the office of the District South Langowan withdetermination power / influence of 76.7%; meaning that developments in labor discipline by 76.7%determined / influenced by camat supervision.Keywords: Monitoring, Work Discipline